Pollination of Anthurium (Araceae) by derelomine flower weevils (Coleoptera: Curculionidae) - Nico M Franz (Revista de Biología Tropical, 2007)
Cyclanthura flower weevils (Coleoptera: Curculionidae: Derelomini) are identified for the first time as pollinators of multiple species of Anthurium (Araceae) in Costa Rica. The weevils are present on the inflorescences in small numbers during the pistillate and staminate phase of anthesis, and consume plant tissues and pollen. The individuals of one species of Cyclanthura can visit several Anthurium species within the same locality. They also engage in reproductive activities and are likely to oviposit into the flowers. The mating strategies suggest that sperm precedence selects males that are able to secure their position as the last partner prior to oviposition. Rev. Biol. Trop. 55 (1): 269-277. Epub 2007 March. 31. Por primera vez se informa que algunos curculiónidos de flores de Cyclanthura (Coleoptera: Curculionidae: Derelomini) polinizan varias especies de Anthurium (Araceae) en Costa Rica. Los curculiónidos están presentes en las inflorescencias en pequeñas cantidades durante la fase pistilada y estaminada de la antesis, y consumen tejidos de la planta y polen. Los individuos de una especie de Cyclanthura pueden visitar varias especies de Anthurium en la misma localidad ; también se ocupan en actividades reproductivas y probablemente ovipositan en las flores. Las estrategias de apareamiento sugieren que la competencia a nivel de gametos selecciona favorablemente al último macho en la secuencia de apareamiento de la hembra, pues éste deposita su semen justo antes de que ella oviposite.